Implementation Of River Transport Safety Regulation In Speedboat In Pier 16 Ilir of Palembang - Ilham, Chairul Insani; D.A, Dahlia; Febriansyah, Febriansyah (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2020)
In general, ship accidents are caused by the lack of implementation of shipping safety, partly because the ship does not meet shipping quality, safety equipment not available on the ship, overloaded loads and lack of supervision from related parties, and the low competence of the crew. Regulations regarding the safety standards for river, lake and crossing transportation are regulated in the Decree of the Minister of Transportation number: KM. 25 of 2015 concerning River, Lake and Crossing Transportation Safety Standards. The average value of the implementation of speedboat on regulations governing the safety of river and lake transportation at Pier 16 Ilir of Palembang is 81 or good enough (CB), consisting of several aspects, namely implementation of safety aspects, Implementation of aspects of human resources (HR), Implementation of aspects of port facilities, Implementation of aspects of standard port operations, Implementation of environmental aspects governing prevention and prevention of pollution from ships and ports.